Decoupling gaseous hydrogen production from liquid water using a magnetic‐photo‐thermal coupling reactor. Issue 11 (16th August 2022) - Wang, Shujian; Lu, Kejian; Hu, Anlan; Li, Naixu; Feng, Yeti; Jing, Dengwei; Liu, Maochang
Abstract: Taking monolithic TiO2 /nickel foam as a model photocatalytic material, we hereby report the application of magnetic‐photo‐thermal coupling field toward enhanced solar photocatalytic hydrogen production. This enhancement is attributed to the increased temperature induced by eddy current effect and effective charge separation caused by the electric field force under the alternating magnetic field condition. Particularly, we demonstrate that a proper set of the position of the monolithic catalyst relative to the reaction solution, that is, at the water‐air interface, will lead to a further enhancement of the photocatalytic activity because of the improved mass transfer property of the reactants, with a hydrogen evolution rate of 104.3 μmol h −1 . Specifically, the increased temperature of the catalyst leads to the rapid evaporation of water. Hydrogen generation is thus decoupled from liquid water, avoiding kinetically disfavored bubble formation. This work provides a novel strategy to facilitate photocatalytic performance with the application of external field.